The determinants of firm growth and profitability : Comparative case study between stable and high growth firms in Nigeria - Odunsi, Sadiq (My University, 2021)
Firm growth has been receiving a lot of attention from researchers over the years. This is because of their significant contribution to the economy through job creation and economic development. However, there is still no single theory that can adequately explain the growth of new ventures (Gibb & Davies 1990). This research aims to find out the factors that contribute to firm growth and profitability in emerging economies. The research is approached by first reviewing the previous literatures on firm growth with a specific focus on four categories of growth variables: founder characteristics, strategy, finance, and business environment. Each of the growth variables are examined in detail to find out how they contribute to firm growth as well as interact with each other. The theory concludes by examining the relationship between growth and profitability because only a few studies have investigated this relationship (Davidsson et al. 2005). The empirical data was collected in five semi-structured interviews. The case companies of the research are Printivo, Wakanow, Jobberman, Drinks.ng, and OList. The founder/CEO of the firms provided the research data. The results of this study revealed that founder characteristics is the most important growth factor, it influences all other variables. The thesis also identified several growth challenges in emerging economies and suggests ways for managers to navigate them.
Keywords: enterprises; business; Nigeria; corporate strategies; growth companies; business environment; growth; finance; emerging markets; fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development